2022
DOI: 10.1093/mnras/stac3634
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the interplay between SIDM and baryons in MW haloes: defining where baryons dictate heat transfer

Abstract: We present a new set of cosmological zoom-in simulations of a MW-like galaxy which for the first time include elastic velocity-dependent self interacting dark matter (SIDM) and IllustrisTNG physics. With these simulations we investigate the interaction between SIDM and baryons and its effects on the galaxy evolution process. We also introduce a novel set of modified DMO simulations which can reasonably replicate the effects of fully realized hydrodynamics on the DM halo while simplifying the analysis and lower… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…The MW host halo exhibits a ∼1 kpc core in our SIDM simulation, which is expected given that our cross section is greater than ∼0.1 cm 2 g −1 at the MW halo velocity scale (e.g., Nadler et al 2020a). Note that this core is not expected to remain in a full hydrodynamic setting because SIDM efficiently responds to a baryon-dominated central gravitational potential, thus regenerating a cusp (Kaplinghat et al 2014;Sameie et al 2018;Robles et al 2019;Rose et al 2023).…”
Section: Cosmological Zoom-in Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MW host halo exhibits a ∼1 kpc core in our SIDM simulation, which is expected given that our cross section is greater than ∼0.1 cm 2 g −1 at the MW halo velocity scale (e.g., Nadler et al 2020a). Note that this core is not expected to remain in a full hydrodynamic setting because SIDM efficiently responds to a baryon-dominated central gravitational potential, thus regenerating a cusp (Kaplinghat et al 2014;Sameie et al 2018;Robles et al 2019;Rose et al 2023).…”
Section: Cosmological Zoom-in Simulationsmentioning
confidence: 99%
“…In future work, it will be particularly interesting to perform hydrodynamic simulations in the presence of core collapse. We expect that the cuspy density profiles of collapsed halos remain resilient to feedback as self-interactions can redistribute energy rapidly (e.g., see Sameie et al 2021;Rose et al 2023 for studies of MW-mass SIDM halos). This may provide a mechanism to form compact dwarf galaxies in SIDM even when feedback is strong.…”
Section: Future Workmentioning
confidence: 99%
“…It has been shown that for galaxies with Milky Way-like masses and above the interplay of baryons and self-interactions can lead to cuspier density profiles than in CDM (e.g. Despali et al 2019;Rose et al 2022). In principle, baryons could also affect the ability to constrain the angular dependence with the abundance of satellites.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies were performed not only with DM-only (DMO) simulations but also within hydrodynamical cosmological simulations (e.g. Vogelsberger et al 2014;Robertson et al 2019Robertson et al , 2020Rose et al 2022;Mastromarino et al 2023;Rahimi et al 2023). They are well-motivated for different angular dependencies, including forward-enhanced crosssections from light mediator models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For smaller self-interacting cross sections, the velocity distribution is non-Maxwellian, while for the velocity-dependent models, the velocity distribution is close to those extracted from collision-less DM-only simulations. High resolution SIDM simulations including baryons have recently become available [44][45][46]. Yet, a study of the local DM distribution and its implications for DM direct detection using such simulations had not been performed and is the aim of this work.…”
Section: Introductionmentioning
confidence: 99%